Feasibility of Noninvasive Diagnosis of Spinal Vascular Diseases Using Time-Resolved Angiography With Stochastic Trajectories - Wei, Xiao-Er; Li, Ming-Hua; Qiao, Rui-Hua; Yu, Wei-Bin; Li, Yue-Hua (Frontiers in Neurology, 2021)
Background and Purpuse: To determine the feasibility of time-resolved angiography with stochastic trajectories (TWIST) in the diagnosis of spinal dural arteriovenous fistula (SDAVF) and perimedullary arteriovenous fistula (PAVF). Methods: A total of 11 negative patients with TWIST examination were retrospective analyzed and then 18 patients with suspected spinal vascular diseases underwent TWIST. For negative patients, Adamkiewicz artery (AKA), great anterior radiculomedullary vein (GARV) and anterior spinal artery (ASA) were retrospective analyzed. In patients, the results of TWIST were compared with those of DSA. Results: The displaying rates of the ASA, AKA and GARV in 11 negative patients were 100%, 90.9% and 90.9%, respectively. The AKA and GARV were separated on TWIST. Of 18 patients, 11 and three were diagnosed with SDAVF and PAVF, respectively. The spinal cord vascular malformation diagnosed on TWIST was consistent with DSA with an excellent intermodality agreement (Kappa=0.92, p<0.001). The feeding artery and side of all 11 SDAVF patients were displayed on TWIST and the results were consistent with DSA. For PAVF patients, the feeding artery in two patients and the sides as displayed on TWIST were consistent with DSA. Conclusions: TWIST enables the differentiation of the spinal artery and vein and the differential diagnosis of SDAVF and PAVF.